School administrator's factomatic - Shockley, Robert J., 1921-; Tocha, Robert; Tracy, Francis G. (Englewood Cliffs, N.J. : Prentice Hall, 1992)
The role of the superintendent of schools. The role of the central office and area office. The role of the principal. How to deal with problem situations. Dealing with the unions, Dealing with classified employees...
Keywords: Education; School management; School personnel management -- United States -- Handbooks, manuals, etc